Prevalence and distribution of blaCTX-M, blaSHV, blaTEM genes in extended- spectrum β- lactamase- producing E. coli isolates from broiler farms in the Philippines - Romeo S. Gundran (2019)
BACKGROUND: Antimicrobial resistance is a worldwide problem causing serious health threats. Escherichia coli is one of the most important bacteria that causes resistance problem. These bacteria produce an enzyme called extended-spectrum β-lactamase (ESBL) that allows it to become resistant to a wide variety of penicillins and cephalosporins. Currently, no information or published studies on ESBL-producing E.coli in broilers are available in the Philippines. This cross-sectional study was conducted to determine the prevalence and distribution of extended-spectrum β-lactamase (ESBL)-encoding genes, blaCTX-M, blaSHV, and blaTEM, among E. coli isolates from broiler farms in Luzon, Philippines. RESULTS: Results showed a farm prevalence of 66. 67%. A total of 69 (44.23%) ESBL-producing E. coli were isolated from boot swabs and cloacal swab samples from broiler farms. All major blaCTX-M groups except blaCTX-M-25 group were identified in the isolates. The most prevalent group was blaCTX-M-1, 72.46% (CI: 60.38-82.54%), followed by blaCTX-M-2, blaCTX-M-9 group and blaCTX-M-8. The blaTEM and blaSHV genes were identified in 57.97 and 27.54% of isolates, respectively. The blaCTX-M and blaTEM were the most common gene combinations (33.33%). Coexistence of blaCTX-M types was observed in 50 (73.53%) isolates. CONCLUSION: This study shows the high prevalence, diversity of patterns and coexistence of ESBL genes in the E. coli isolates from cloacal and boot swabs from broiler farms which pose risks of possible transmission to the environment, other animals and human.